2009
DOI: 10.3846/1392-8619.2009.15.490-521
|View full text |Cite
|
Sign up to set email alerts
|

Environment Factors of Energy Companies and Their Effect on Value: Analysis Model and Applied Method

Abstract: Practical tasks related to property management and disposal in energy companies can be solved only if the actual property value of these companies is known. Traditional practical property valuation methods are based on the analysis of incurred property development costs or financial indicators of activities and are inadequate to account for the influence of environment factors on corporate activities and, in turn, on the value of companies. An analysis model for environment factors affecting energy companies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…DSP instrumento parinkimas priklauso nuo uždavinio ir kriterijų, pagal kuriuos priimamas spren dimas, skaičiaus [30].…”
Section: Energetikos Sektoriaus Daugiakriterinių Sprendimų Paramos Inunclassified
“…DSP instrumento parinkimas priklauso nuo uždavinio ir kriterijų, pagal kuriuos priimamas spren dimas, skaičiaus [30].…”
Section: Energetikos Sektoriaus Daugiakriterinių Sprendimų Paramos Inunclassified
“…The development and use of MCDM tools in energy-sector decision-making were primarily determined by the liberalisation of energy markets, implementation of the principles of sustainable development, involvement of stakeholder groups in energy-sector decisionmaking, and the attempts to make sure the general public was represented in policy making. An analysis of literature revealed that, in the energy industry, MCDM tools are most often used to address such issues as energy policies and relevant environmental aspects, but rarer to analyse the choice of energy generation technologies [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…This could be demonstrated by calculating the average external air temperature of the coldest five-day period t e5 as one of the most important temperatures, which is used for thermal protection of the enclosing structures and calculation of thermal power of the heating and ventilation systems. Due to the fact, that a five-day period is related to discrete events, the direct application of the analytical expression for the probability density function of a normally distributed random value with parameters that characterize a year in tote would be difficult because such expression would describe the temperature behaviour of a continuous time interval (Šliogerienė et al 2009;Wang et al 2011). Consequently, numerical simulation using software that generates daily temperatures with sensors of pseudorandom values is required.…”
Section: The Probabilistic-statistical Modelling In the Selection Of mentioning
confidence: 99%